Determinación de los índices de la calidad de agua mediante la presencia de macro y micro invertebrados del humedal Illos del sector Chaloacocha del parque Nacional LLanganates en la provincia de Cotopaxi - Arévalo Pacheco, Byrom Jonathan (2017)
The present investigation was carried out in the National Park Llanganates province of Cotopaxi, since it has a varied lacustrine system which are in the natural state, so we chose to carry out our present investigation to determine the index of water quality, Through the presence of macro and micro invertebrates as natural bioindicators in the Illos wetland that is located in the sector Chaloacocha. To evaluate water quality indexes, methodologies such as Ephemeroptera, Plecoptera, Trichoptera (EPT) and Biological Monitoring Working Party (BMWP) were used, the Shannon - Weaver index was used in ecology or other sciences to measure specific biodiversity. Similarly, it was possible to deduce that the most common and abundant species detected at the sampling points correspond to the families of Hyalellidae, Notonectidae, Planariidae, and Glosiiphoniidae, and the families with the lowest abundance are Oligochaeta, Scirtidae, Sphaeriidae, Libellulidae, Cypridae. In what corresponds to the diatoms was taken as the main reference their presence in each of the established sampling points, seven species were identified respectively of micro algae taking into account their degree of tolerance and what they represent biologically for the Ecological status of the wetland Illos. As a result of the investigation, it was also possible to conclude that, within the physical, chemical and microbiological parameters, it was determined that the established variables do not exceed the limits established in the current water quality standard (TULSMA Book VI, Annex I in Table 2). That is, in the Illos wetland, it is evident that no strategies have been implemented on the management of the tributaries that enter the wetland, so the established indicators determine that this medium contaminated.